Evaluating democratic governance: A bottom up approach to European Union enlargement. - Rose, Richard (My University, 2007)
Der Beitrag vergleicht die EU-Kriterien für die Bewertung von Beitrittskandidaten mit Demokratie-Indices und greift für eine "Bottom-up-Evaluation" der demokratischen Governance in Bulgarien, Rumänien, Kroatien und der Ukraine auf die Daten der 13 Länder umfassenden Meinungsumfragen des "New Europe Barometer" zurück. Die Ergebnisse werden Position für Position der Mindestbewertung von demokratischer Governance für die acht mittel- und osteuropäischen Beitrittsländer des Jahres 2004 gegenübergestellt. Die Faktoranalyse bestätigt statistisch, dass diese Massstäbe multi-dimensional sind. Demokratische Governance kann nicht auf einen eindimensionalen Demokratie-Index reduziert werden. Die Vorteile, in Kategorien der demokratischen Governance zu denken stellen sich nicht nur für die Diagnose und Beschreibung von staatlichen Reformen, sondern auch für die wissenschaftliche Begleitforschung von Demokratisierungsprozessen.

Although analyses of democracy and governance may be complementary rather than in conflict, they are not identical. This article compares the EU criteria for evaluating applicants for membership with those of democracy indexes. It uses data from the 13-country New Europe Barometer surveys of public opinion to provide a bottom up evaluation of democratic governance in Bulgaria, Romania, Croatia and Ukraine. The results are compared, point by point, with the minimum evaluation of governance in the eight Central and East European countries admitted to the EU in 2004. Factor analysis confirms statistically that these measures are multi-dimensional; in other words, democratic governance cannot be reduced to a one-dimensional index of democracy. The conclusion emphasizes the advantages of thinking in terms of democratic governance not only for diagnosing and prescribing governmental reforms but also for academics monitoring democratization as a process that may only be partially successful.
Keywords: Gesellschaftsordnung; Demokratie; Bewertung; Messung; Demokratietheorie; Governance; EU-Beitrittsland; Index; Demokratisierung; Evaluation; Staatsreform; Reformprozess